A COMPARATIVE STUDY OF PRIMARY 4 STUDENTS’ ACADEMIC ACHIEVEMENT AND PERCEPTION OF LEARNING CHINESE AS A FOREIGN LANGUAGE UNDER AN INQUIRY-BASED LEARNING METHOD AT AN INTERNATIONAL SCHOOL IN BANGKOK, THAILAND - MEESIN, SUNANTHA; KARNJANAPUN, SUPIT (Scholar: Human Sciences, 2022)
The objective of conducting this comparative research was to determine students’ academic achievement in learning Chinese while being instructed under the teaching methodology of inquiry-based learning method in learning Chinese as a foreign language at an international school in Bangkok. How has learning under the inquiry-based learning method increased students’ academic achievement and sufficiency for Primary 4 students, which prepared them sufficiently to pass their HSK (Hanyu Shuiping Kaoshi) Chinese proficiency test at their respective Chinese levels? This study examined both the effectiveness of the learning methodology and students’ perception of their academic performance to determine how inquiry-based learning methods work in learning a foreign language. A pre-test and post-test were given to Primary 4 students in a Chinese class. The research was conducted from May 2020 to June 2020 in Chinese class. The topic was in Unit 1, "Greeting," which emphasized classroom activity, friends, and family. The lessons were conducted for four weeks, with 3 hours of class per week lasting for a total duration of 60 minutes. The sample size of this study was 18 students being instructed under the inquiry-based learning method. Results indicated that the student’s academic achievement and performance in the Chinese language have increased in percentage under the inquiry-based learning methodology. The findings showed that the inquiry-based learning method results in higher achievement in students’ academic performance. Students’ perception of learning Chinese under the inquiry-based learning method was effective. Therefore, the findings of the study indicated a 1 M.Ed. in Curriculum and Instruction, Chinese Language Teacher, Raffles American School, No.15, Moo.15 Bangna-Trad Road, Bangkaew, Bang Phli, Samut Prakan, Thailand. sunanthameesin@gmail.com 2 Ph.D., Associate Professor, Graduate School of Human Sciences, Assumption University, 592/3 Ramkhamhaeng Road, Soi 24, Hua Mak, Bang Kapi, Bangkok, Thailand. supitkrn@au.edu Scholar: Human Sciences, ISSN 2586-9388, Vol.14 No.2 (Jul.-Dec. 2022) 433 significant difference in gains instructed under the inquiry-based learning method at a significance level of .05 found in this study. Students achieved higher when exposed to inquiry-based learning methods in learning Chinese as a foreign language.